2022
DOI: 10.1111/nmo.14364
|View full text |Cite
|
Sign up to set email alerts
|

Pictograms are more effective than verbal descriptors in Spanish for bloating and distension

Abstract: Bloating in English is defined as the subjective sensation of an increase in abdominal girth, while abdominal distension is the visible or true increase in abdominal girth. 1 The first one is a symptom, while the second one is both a symptom and a clinical sign. In addition, bloating and distension can coexist and they are very commonly reported by patients and subjects in the general population. 2 Their underlying mechanism is not completely elucidated; however, bloating may be related to gut hypersensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…In addition, the pictograms showed a positive agreement with the physician's diagnosis and a negative agreement with VDs, in both groups of patients. Finally, these pictograms were more sensitive and specific than the VDs 3 . The above findings suggested that the bloating/distension pictograms could be used in the clinic, in clinical trials as well as in epidemiological studies in Spanish‐speaking countries.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, the pictograms showed a positive agreement with the physician's diagnosis and a negative agreement with VDs, in both groups of patients. Finally, these pictograms were more sensitive and specific than the VDs 3 . The above findings suggested that the bloating/distension pictograms could be used in the clinic, in clinical trials as well as in epidemiological studies in Spanish‐speaking countries.…”
Section: Introductionmentioning
confidence: 82%
“…There is no term for bloating in Spanish and abdominal distension is a very technical expression for people to understand, making it very difficult to investigate these symptoms in Spanish‐speaking populations like in Mexico 1 . Therefore, we previously validated the use of pictograms to assess the presence of bloating and/or distension in patients from a general gastroenterology clinic and with IBS by Rome III criteria in this country 3 . In these studies, we found that “inflammation” was the most frequent VD used by the patients and distension was commonly interpreted as a sensation (“inflammation”) and/or an increase in abdominal girth 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations